Deoxycholate, an Endogenous Cytotoxin/Genotoxin, Induces the Autophagic Stress-Survival Pathway: Implications for Colon Carcinogenesis - Claire M. Payne; Cheray Crowley-Skillicorn; Hana Holubec; Katerina Dvorak; Carol Bernstein; Mary Pat Moyer; Harinder Garewal; Harris Bernstein (Journal of Toxicology)
We report that deoxycholate (DOC), a hydrophobic bile acid associated with a high-fat diet, activates the autophagic pathway in non-cancer colon epithelial cells (NCM-460), and that this activation contributes to cell survival. The DOC-induced increase in autophagy was documented by an increase in autophagic vacuoles (detected using transmission electron microscopy, increased levels of LC3-I and LC3-II (western blotting), an increase in acidic vesicles (fluorescence spectroscopy of monodansycadaverine and lysotracker red probes), and increased expression of the autophagic protein, beclin-1 (immunohistochemistry/western blotting). The DOC-induced increase in beclin-1 expression was ROS-dependent. Rapamycin (activator of autophagy) pre-treatment of NCM-460 cells significantly (P<.05) decreased, and 3-MA (inhibitor of autophagy) significantly (P<.05) increased the cell loss caused by DOC treatment, alone. Rapamycin pre-treatment of the apoptosis-resistant colon cancer cell line, HCT-116RC (developed in our laboratory), resulted in a significant decrease in DOC-induced cell death. Bafilomycin A1 and hydroxychloroquine (inhibitors of the autophagic process) increased the DOC-induced percentage of apoptotic cells in HCT-116RC cells. It was concluded that the activation of autophagy by DOC has important implications for colon carcinogenesis and for the treatment of colon cancer in conjunction with commonly used chemotherapeutic agents.